The core self-evaluations, psychological capital, and academic engagement: a cross-national mediation model - Paloș, Ramona; Samfira, Elena Mirela; Vîrgă, Delia; Purić, Daliborka (Frontiers in Psychology, 2023)
An academic environment with continuously more demanding tasks requires students to capitalize on their strengths to meet the challenges and engage in learning experiences. Engaged students are deeply involved in their work, are strongly connected with their studies, and are more successful in academic tasks. The present study aimed to test a model in that core self-evaluations (CSE) predicts academic engagement (AE) directly and indirectly by increasing personal resources (i.e., psychological capital; PsyCap) in the case of two different samples, Romanian and Serbian. Data were collected through three online questionnaires from 672 undergraduate students (Romania – 458; Serbia – 214). The findings confirmed that CSE was positively related to PsyCap, which was positively associated with AE, and PsyCap mediates the relationship between the two variables in both samples. A positive evaluation of one’s characteristics (high CSE) mainly affects the cognitive and emotional mechanism of appraising the academic-related tasks one encounters (high PsyCap), ultimately shaping their motivation and engagement. These results pointed out the importance of the CSE and PsyCap that support each other and increase students’ AE, explaining the mediating mechanism of PsyCap. Also, they provide insight into the students’ engagement from two different cultural and educational contexts, being helpful to universities in their effort to increase students’ engagement.